History, historians and development policy a necessary dialogue - Bayly, Christopher Alan 1945-2015; Rao, Vijayendra; Szreter, Simon 1957-; Woolcock, Michael 1964- (Manchester University Press, 2011)
Leading historians and policy advisors explore the implications of incorporating historical sensibilities into key development policy issues